Heptapharmacological activity of Quercetin-3-O-phosphate against lung cancer pathways - Maryam Abdulrahman Alahdal; Hadil Alahdal; Najat Binothman; Majidah Aljadani; Nawal Helmi; Maryam A. AL-Ghamdi; Alaa Hamed Habib; Misbahuddin Rafeeq; Tahani Bakhsh; Hadeel A. Alsufyani; Abeer Al Tuwaijri (PLoS ONE, 2026)
Lung cancer is one of the leading causes of cancer-related deaths globally, with smoking being the primary risk factor, though environmental exposures and genetic mutations also play significant roles. Lung cancer arises when abnormal lung cells grow uncontrollably, leading to over 2 million new cases and nearly 1.8 million deaths globally. Drug resistance, especially to targeted therapies, is a key challenge, as tumours often adapt and become unresponsive. Multitargeted drug design, which targets multiple pathways involved in tumour growth, offers a promising solution to overcome resistance and improve treatment efficacy. In this study, we identified several lung cancer–associated proteins: CK2, Ran–Importin β complex, HNGF, Human Survivin, CRK-II adaptor protein, AKR1B10, and tRNA dihydrouridine synthase 2, with respective PDB IDs 1JWH, 1IBR, 1SG1, 1XOX, 2DVJ, 4XZL, and 4XP7. We conducted molecular docking using DrugBank’s library, employing HTVS, SP, and XP, followed by pose processing with MM/GBSA. Our multitarget docking analysis identified Quercetin-3-O-Phosphate as the top compound, a quercetin derivative found in fruits and vegetables such as onions, apples, berries, broccoli, and citrus. The compound showed docking and MM/GBSA scores ranging from −5.835 to −11.627 Kcal/mol and −14.28 to −47.07 Kcal/mol, respectively, and the key interacting residues with their counts include 10ASP, 9LEU, 9LYS, 7ALA, 7ARG, 7TYR, 6GLN, 5ASN, 5GLU, 5ILE, and 5VAL. We also performed and analysed DFT and pharmacokinetics in detail, which supported its further evaluation as it met all the required criteria. We conducted a 5 ns WaterMap simulation, which confirmed the interactions and highlighted key hydration sites that support the complex’s stability. A 100 ns MD simulation using the TIP3P water model showed minimal deviation and fluctuations, indicating stable interactions and the trajectories used for MM/GBSA calculations, assessing binding free, which reinforced the stability of the complexes and helped rank the best candidates. All results indicate that Quercetin-3-O-Phosphate holds strong potential for lung cancer treatment, though experimental validation is needed for clinical confirmation.